Clinical and Epidemiological Characteristics of Diabetic Ketoacidosis in Older Adults. Issue 6 (5th March 2020) - Schwarzfuchs, Dan; Rabaev, Elena; Sagy, Iftach; Zimhony‐Nissim, Noa; Lipnitzki, Inna; Musa, Hadeel; Jotkowitz, Alan; Brandstaetter, Evgenia; Barski, Leonid
Abstract : OBJECTIVES: Much of the research previously done on diabetic ketoacidosis (DKA) was based on a young population with type 1 diabetes mellitus (type 1 DM). But substantial numbers of DKA episodes occur in patients with a prior history of type 2 diabetes mellitus (type 2 DM). There is a lack of Data are lacking about DKA in older adults. The aims of this study were to analyze the clinical characteristics and outcomes of older adult patients with DKA. DESIGN: Retrospective matched cohort study of adult patients hospitalized with DKA between 2004 and 2017. SETTING: Soroka University Medical Center, Be'er Sheva, Israel. PARTICIPANTS: The clinical characteristics of DKA patients 65 years and older were compared with patients younger than 65 years. MEASUREMENTS: The primary outcome was in‐hospital mortality. RESULTS: The study cohort included 385 consecutive patients for whom the admission diagnosis was DKA: 307 patients (79.7%) younger than 65 years (group 1), and 78 patients (20.3%) older than 65 years (group 2). Patients in group 2 compared with group 1 had a significantly higher Charlson index (6 [6–6] vs 6 [6–7]; P < .0001) and DM with target organ damage (24.4% vs 6.2%; P < .0001). Patients in group 2 compared with group 1 had more serious disease according to results of laboratory investigations. The total in‐hospital mortality rate of patients in group 2 was 16.7% compared with 1.6% in patients in group 1 in a sex and co‐morbidities matched analysis ( P = .001). CONCLUSIONS: DKA in older adults is a common problem. The serious co‐morbidities and precipitating factors such as infection/sepsis, myocardial infarction, and cerebrovascular accidents, may explain the severity of the problem of DKA in older adults and the high rate of mortality of these patients. DKA appears to be a lifethreatening condition in older adults. The alertness of physicians to DKA in older adults, timely diagnosis, proper treatment, and prevention are cornerstones of care. J Am Geriatr Soc 68:1256–1261, 2020.